Pre-rift evolution of Malawian high-grade basement rocks - Huang, Leslie (Department of Geological Sciences, 2017)
There is some controversy in terms of the basement geology of Malawi which ultimately stems from the overall lack of metamorphic studies conducted in the area. The geological complexity of Malawi comes from that fact that it sits at the intersection of three major orogenic belts: The Palaeoproterozoic Ubendian Belt, Mesoproterozoic Kibaran/Irumide Belt, and Pan African Mozambique Belt. Its complexity makes it difficult to unravel, especially in terms of identifying features of older orogenic events which have already experienced multiple metamorphic overprinting from subsequent events. This thesis provides a more detailed pre-rift evolution of the Malawian basement rocks by reporting ages and P-T conditions from four localities surrounding Lake Malawi, namely Chilumba, Mlowe, Maganga, and Mangochi. Results reveal that at 1985-1974 Ma, garnet-cordierite granulites were equilibrated under conditions of 760°C at 4.5-5 kbar possibly as a result of subduction-related magmatism. Subsequently, at 1100 Ma, charnockites were emplaced and metamorphosed under peak conditions of 770-780°C at 4.3-6 kbar due to Kibaran-age magmatic underplating. Remnants of the Irumide/Kibaran Orogeny is relatively scarce throughout Malawi and although the Mangochi charnockites were emplaced during Kibaran-age tectonism, it also experienced at least two different metamorphic events thereafter. The first occurred either during early stages of the East African orogen or Rodinia break-up at 900-800 Ma while the second occurred during the late stages of the East African orogen at 650-600 Ma. Possible remnants of the Kuunga Orogeny are recorded in Chilumba and Maganga as an amphibolite facies metamorphic event which took place around 570 Ma under peak conditions of roughly 660-670°C at 6-8 kbar. Findings of this study have not only provided a more detailed metamorphic history of Malawi but also paved way for future studies in the area to further explore why similar rocks found in such close proximity to each other preserve vastly different tectonic environments.